2016
DOI: 10.1038/srep28553
|View full text |Cite
|
Sign up to set email alerts
|

Hydration Repulsion between Carbohydrate Surfaces Mediated by Temperature and Specific Ions

Abstract: Stabilizing colloids or nanoparticles in solution involves a fine balance between surface charges, steric repulsion of coating molecules, and hydration forces against van der Waals attractions. At high temperature and electrolyte concentrations, the colloidal stability of suspensions usually decreases rapidly. Here, we report a new experimental and simulation discovery that the polysaccharide (dextran) coated nanoparticles show ion-specific colloidal stability at high temperature, where we observed enhanced co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 53 publications
1
18
0
Order By: Relevance
“…The concept of specific ion effects has been recognized for decades, yet the microscopic details, physical origins, and potential implications have been controversial, leading to significant debate in the scientific community 2739 . Recent adhesion force measurements using atomic force microscopy (AFM) demonstrated interesting ion-specific behavior of nanomaterials in reservoir fluids 40 .…”
Section: Introductionmentioning
confidence: 99%
“…The concept of specific ion effects has been recognized for decades, yet the microscopic details, physical origins, and potential implications have been controversial, leading to significant debate in the scientific community 2739 . Recent adhesion force measurements using atomic force microscopy (AFM) demonstrated interesting ion-specific behavior of nanomaterials in reservoir fluids 40 .…”
Section: Introductionmentioning
confidence: 99%
“…This extreme low efficiency can be attributed to reduced hydration of the hydroxy groups on the amine ethoxylate heads of the surfactant molecules in Brine 1 as compared in Brine 2, leading to higher interfacial tension between the CO 2 and the aqueous phase in Brine 1. It has been reported that hydration of carbohydrates increases with increasing the concentration of calcium ions (Ca 2+ ) in water, especially at high temperatures (i.e., 90 °C) 45 . Considering that Brine 2 contains twenty times more Ca 2+ ions than Brine 1, similar effects are expected to happen here.…”
Section: Resultsmentioning
confidence: 99%
“…At each MD time step, we first summed the total forces exerted on all the atoms that construct the SAM, and then calculated by dividing the sum of total forces on SAM by the projected area of SAM on the x–y plane to give the pressures. Finally, the potential of mean forces (PMF) were calculated by , where Π( d ) were the pressures measured at each d as described above (i.e., pressure-distance curves) and we used the max distance d = 2.7 nm as the reference state 19 , 33 .…”
Section: Methodsmentioning
confidence: 99%
“…Surface functionalization has been critical for the engineered nanoparticles to achieve the desired compatibility in the target environments. Hydrophilic coatings such as polyols and polysaccharides are attractive for their good biocompatibility and solubility in saline aqueous environments 17 19 . Nevertheless, polyols and polysaccharides may form extensive adsorption on mineral surfaces 20 .…”
Section: Introductionmentioning
confidence: 99%